A method and device for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition
By adding magnesium chlorite to the anode region of the electrolytic device and stirring, the process of separating magnesium ion mass transfer using a polytetrafluoroethylene separator is solved, and the high energy consumption and uneven morphology of the preparation of hexagonal sheet magnesium hydroxide in the prior art is solved. , realizes a low-cost and high-efficiency continuous preparation, and the product has good dispersion and crystallinity.
Patent Information
- Application Number
- CN202310063203.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-01-16
AI Technical Summary
The prior art has problems such as high energy consumption, high equipment requirements, poor continuous production capacity and uneven product morphology when preparing hexagonal sheet magnesium hydroxide.
By using continuous electrodeposition method, by adding magnesium ion mass transfer process and stirring in the anode region of the electrolytic device, the magnesium ion mass transfer process is separated from the electromigration process by using a polytetrafluoroethylene separator, the initial concentration of Mg2+ in the cathode region is controlled to be 0, and the The influence of cathode plates on product growth, expanding the cathode reaction zone to improve product dispersion and crystallinity.
The product has achieved a low-cost and high-efficiency continuous preparation of hexagonal sheet magnesium hydroxide, with good dispersion, crystallinity and morphological regularity, reducing equipment requirements and energy consumption.
Smart Images

Figure CN115976544B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method and a device for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition, belonging to the field of inorganic material preparation. Background Art
[0002] Mg(OH)2 crystals belong to the divalent metal hydrate family and have a CdI2-type layered structure with continuous hexagonal Mg 2+ ion layers and OH- ion layers are stacked on top of each other, Mg 2+ OH - Six times coordinated to form Mg(OH)6 4- Growth unit. In each unit cell, Mg 2+ The node position located at the origin of the hexagonal lattice, OH - In three Mg 2+ The upper and lower sides of the triangular plane formed are cross-distributed, Mg 2+ The coordination number is 6, with 2 OH groups above and below - Therefore, Mg(OH)2 is equivalent to two layers of OH - and a layer of Mg 2+ The three-layer sandwich structure of magnesium hydroxide is a typical layered structure compound. The three layers of ions form a unit layer. Each unit layer is connected by ionic bonds, and the layers are mainly composed of weak hydrogen bonds.
[0003] Based on its unique structure and properties, magnesium hydroxide has a wide range of applications in flame retardancy, adsorption, medicine, etc. The general preparation methods include direct precipitation, hydrothermal method, sonochemical synthesis method, microemulsion method, electrodeposition method, etc. At present, high-quality hexagonal flaky magnesium hydroxide is mainly prepared by hydrothermal method and long-term aging or active magnesium oxide hydration method. The hydrothermal method is a method of promoting the free growth of crystals in a high-temperature and high-pressure reactor. Generally, a modifier is added to the method to control the morphology and particle size of the grains. The method is highly inclusive, and the choice of raw materials and precipitants is diverse. The magnesium hydroxide prepared by this method has the characteristics of good dispersibility, high crystallinity, and controllable morphology and particle size. However, the energy consumption is high under high temperature and high pressure conditions and it is not conducive to continuous production. At the same time, the reaction is generally carried out under strong alkaline conditions, which has high requirements for the reaction equipment. Generally, there will be a layer of polytetrafluoroethylene film in the reactor, which increases the production cost. The hydration method is relatively simple. It mainly uses active magnesium oxide as a raw material to generate magnesium hydroxide through a hydration reaction. The method has a simple process and high product quality, but it has high requirements for raw materials and low cost performance.
[0004] Chinese patent CN201210456958.2 discloses a method for preparing magnesium hydroxide hexagonal nanosheets, which mainly includes the following steps: first, an ammonia solution is added dropwise to a magnesium chloride solution, the obtained suspension is washed several times with deionized water to obtain an intermediate, the intermediate is mixed with sodium dodecyl sulfate into an ethanol solution and then poured into a reactor for hydrothermal reaction, the reaction time is 2 to 24 hours, the reaction temperature is 160 to 180°C, and the product is subsequently treated to obtain a magnesium hydroxide product. This method has a high yield, and the product is a nano-scale hexagonal sheet. The disadvantages are harsh reaction conditions, high energy consumption, high equipment requirements, and poor continuous production capacity.
[0005] Chinese patent CN201710662515.1 discloses a method for preparing uniform hexagonal flaky nano magnesium hydroxide by hydration. The method uses active magnesium oxide as raw material, prepares a magnesium oxide suspension, adds the magnesium oxide suspension to distilled water for hydration under an ultrasonic environment, and after 1 to 5 hours, filters, washes, and dries to obtain uniform hexagonal flaky nano magnesium hydroxide. The product has uniform morphology, good dispersibility, and high quality. Compared with the crystal form control agent, hydrothermal environment, and long-term aging conditions required by the hydrothermal method, the production cycle is greatly shortened and the production cost of the product is reduced. However, this method has high requirements for raw materials, and the higher the activity of the magnesium oxide used, the better the product quality, which increases the production cost to a certain extent.
[0006] Chinese patent CN202110829696.9 discloses a method for preparing hexagonal flaky flame-retardant magnesium hydroxide from natural hydromagnesite, which method crushes and screens natural hydromagnesite in turn; calcines the crushed and screened natural hydromagnesite to obtain active magnesium oxide; screens the active magnesium oxide; uses active magnesium oxide as raw material and deionized water as solvent to prepare a magnesium oxide suspension; places the magnesium oxide suspension into a closed heating device for heating (100-200°C) to react and obtain a solution; takes out the solution and cools it naturally to room temperature to obtain a product, and filters, washes, and dries the product to obtain hexagonal flaky magnesium hydroxide. This method includes three parts: calcination of hydromagnesite, hydration of active magnesium oxide, and hydrothermal modification. In addition to hydromagnesite, no other raw materials or additives need to be added to obtain hexagonal flaky flame-retardant magnesium hydroxide with high crystallinity, good dispersibility, and regular morphology. However, the process is more complicated, the process is longer, and the cost is higher.
[0007] Electrodeposition is a method for mass production of magnesium hydroxide raw powder. This method uses magnesium chloride solution obtained by filtering bischofite dissolved in water as the electrolyte and adopts a conventional double-chamber electrolytic cell. Since the magnesium ion concentration near the cathode plate is very high at the beginning of the reaction, the hydroxide generated on the cathode plate will quickly combine with it to form magnesium hydroxide and adhere to the plate. The high supersaturation, small reaction space and attached growth on the cathode plate cause the magnesium hydroxide to agglomerate severely, forming irregular thin sheets with adhesion between grains, or even a continuous mesh structure. The laser particle size is above 50μm, and the direct application range of the product is small. At the same time, the adhesion of the product to the plate will also cause the cell voltage to increase, and even the reaction cannot proceed normally. This has high requirements for the peeling treatment of the product on the plate. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention provides a method and device for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition. Bischofite (MgCl2·6H2O) and sodium chloride are used as raw materials. Bischofite is added to the anode area of the electrolysis device of the present invention and stirred. At the beginning of electrolysis, Mg in the cathode area is 2+ The initial concentration is 0, and there is a certain concentration of Mg in the anode region. 2 + The effect of the cathode plate on the product growth is reduced or even eliminated by penetrating into the cathode area through the polytetrafluoroethylene diaphragm under the action of electromigration to participate in the reaction. At the same time, the cathode area (reaction area) is expanded to reduce the supersaturation of the reaction, so that the product is directly generated in the cathode reaction area. The hexagonal flaky Mg(OH)2 obtained by this method is a nano-scale grain with good dispersion, and the device has great advantages in low-cost and high-efficiency continuous preparation.
[0009] The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition of the present invention comprises the following steps:
[0010] S1: prepare a sodium chloride aqueous solution with a molar concentration of 0.05-0.2 mol / L;
[0011] S2: adding sodium chloride aqueous solution into the electrolytic cell, heating it to 30-60°C, adding bischofite into the anode region after the temperature stabilizes, and stirring, so that the magnesium ions in the anode region are evenly distributed and the molar concentration is 0.1-0.5 mol / L; wherein a diaphragm is provided in the electrolytic cell, dividing the electrolytic cell into an anode region and a cathode region connected only by the diaphragm; the anode plate is provided in the anode region, and the cathode plate is provided in the cathode region;
[0012] S3: Connect the anode plate and cathode plate to the power supply and set the current density to 0.006~0.02A / cm 2The distance between the cathode plate and the anode plate is 6 to 12 cm. The electrodeposition is carried out for 4 to 12 hours. A white precipitate is obtained in the cathode area. The precipitate is filtered, washed and dried to obtain hexagonal flaky magnesium hydroxide.
[0013] Furthermore, in S1, the sodium chloride aqueous solution is preferably prepared by ultrasonic stirring for 0.1 to 0.5 h to make the sodium chloride aqueous solution evenly dispersed.
[0014] Furthermore, in the step S2, the stirring is performed at a rate of 200 to 1000 r / min, and the stirring time is preferably 30 to 60 s.
[0015] Furthermore, in S3, the washing is preferably performed by washing twice with deionized water and then washing once with anhydrous ethanol.
[0016] Furthermore, in S3, the drying temperature is 60-120° C., and the drying time is 6-12 hours.
[0017] During the electrodeposition process, the feeding time of bischofite circulation is determined according to the change of pH value in the cathode area. The specific determination method is: when the pH value becomes stable and then starts to increase, the feeding is performed when the increase is 1.
[0018] The pH monitoring time interval is preferably 10 min.
[0019] During the electrodeposition process, the conductivity of the electrolyte in the anode region is monitored according to the conductivity to determine the feeding amount of bischofite for circulation, and the feeding amount is the mass of bischofite that makes the molar concentration of magnesium ions in the anode region account for 0.1 to 0.5 mol / L, even if the conductivity returns to the initial value.
[0020] In order to realize the above-mentioned method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition, the present invention also provides a device for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition, comprising an electrolytic cell, a polytetrafluoroethylene diaphragm is arranged in the electrolytic cell body to divide the electrolytic cell body into a cathode area and an anode area, and the anode area and the cathode area are only connected by the diaphragm, a cathode plate is arranged in the cathode area, an anode plate is arranged in the anode area, and a water outlet is arranged on the upper part of the side wall of the electrolytic cell body in the cathode area; the electrolytic cell is also provided with a heating device for controlling the temperature during the electrodeposition process; a stirring device is also arranged in the anode area, and a filter tank is also arranged in the anode area for adding bischofite and filtering out impurities.
[0021] Furthermore, the cathode plate and the anode plate are designed to be distributed in an asymmetric structure.
[0022] Furthermore, a pH probe is provided in the cathode region.
[0023] Furthermore, a conductivity probe is provided in the anode region for monitoring the conductivity of the electrolyte.
[0024] Furthermore, a corresponding plate slot is provided at the location where the cathode plate is provided, and a corresponding plate slot is provided at the location where the anode plate is provided.
[0025] The cathode plate or anode plate is made of acid and alkali corrosion resistant material, preferably a titanium plate with titanium dioxide coated on the surface.
[0026] Furthermore, the heating device is preferably a heating rod, which is connected to a temperature control device, and the temperature control device is used to control the heating of the heating rod, thereby controlling the temperature of the electrodeposition process.
[0027] More preferably, a heating device is provided in the anode region.
[0028] The heating rod is an acid and alkali corrosion resistant heating tube, and more preferably a U-shaped heating rod.
[0029] The stirring device is preferably arranged at the bottom of the anode area, and more preferably the stirring device is an acid- and alkali-resistant corrosion rotor.
[0030] Furthermore, a product precipitation zone is provided at the bottom of the cathode zone.
[0031] The diaphragm is a polytetrafluoroethylene film with a pore size of 0.5 to 10 μm.
[0032] In the cathode region, a large amount of space is left at the bottom of the cathode plate, which facilitates the deposition of the product at the bottom of the cathode region, thereby carrying out continuous production; on the other hand, it prevents the salt solution formed by the salt solution diffused from the anode region to the cathode region from having an adverse effect on the reaction. At the same time, the salt solution concentration is high, and the hexagonal flaky magnesium hydroxide product formed by electromigration mass transfer will first be deposited on the salt solution deposition layer formed in the concentration diffusion process, and settle to the bottom after reaching a certain thickness. The deposition layer of the hexagonal flaky magnesium hydroxide product formed is relatively compact, which makes the hexagonal flaky magnesium hydroxide product have a very high filtration performance. Compared with the hexagonal flaky magnesium hydroxide product prepared by other methods, the filtration time required for the same mass is greatly reduced.
[0033] The distance between the cathode plate and the polytetrafluoroethylene diaphragm of the electrolytic cell is 55% to 70% of the distance between the plates, which is beneficial to the expansion of the cathode area and the control of various conditions in the cathode area during the reaction process.
[0034] The heating rod is equipped with a polyfluoride sleeve, which has strong acid and alkali corrosion resistance. The heating rod is placed in the anode area, and the convection brought by stirring is more conducive to the heat transfer process, making the temperature of the cathode reaction area uniform, stable and easy to control.
[0035] The filter tank is coated with a layer of acid-resistant filter cloth and placed in the anode area. The raw materials are dissolved in the filter tank and diffused into the electrolytic cell under the stirring action of the stirring device. The filter tank is a detachable structure, which is convenient for feeding, filtering and cleaning of the filter cloth.
[0036] The water outlet is arranged in the cathode area and on the back side of the cathode plate. The salt concentration in this area is relatively low. When the liquid level is raised to the height of the water outlet by feeding, the electrolyte (a mixed solution of magnesium chloride and sodium chloride) will flow out of the water outlet to stabilize the liquid level and realize continuous electrolysis. At the same time, the loss of reactants, products, and valuable ions in the solution can be controlled within a very small range.
[0037] Compared with the prior art, the present invention has the following technical effects:
[0038] (1) The present invention uses a low-permeability polytetrafluoroethylene diaphragm to separate the concentration diffusion process and the electromigration process of the magnesium ion mass transfer process. Because a stirring device is provided in the anode area and the cathode area is a static area, the magnesium ions diffused by the concentration difference enter the cathode area and are deposited downward along the diaphragm to the bottom to form a salt solution deposition layer, while the magnesium ions transferred by electromigration enter the cathode reaction area to participate in the reaction, thereby avoiding the problem of uneven magnesium ion concentration and uneven reaction caused by diffusion. At the same time, the problem of excessively high magnesium ion concentration near the electrode plate at the beginning of the conventional electrodeposition method and the problem of uneven morphology and serious agglomeration caused by the product growth attached to the cathode electrode plate are avoided.
[0039] (2) The cathode and anode plates are designed to have an asymmetric structure, which expands the cathode reaction area while ensuring a reasonable plate spacing.
[0040] (3) Compared with conventional electrodeposition, the present invention further adds a sodium chloride aqueous solution, the purpose of which is to ensure that there are sufficient conductive ions in the cathode region of the electrolytic cell at the beginning of deposition so that the electrolysis can proceed normally. At the same time, the presence of sodium ions will reduce the amount of magnesium ions migrating to the cathode to a certain extent, thereby regulating the magnesium ion concentration in the cathode region.
[0041] (4) The method for preparing hexagonal flaky magnesium hydroxide of the present invention is simple, easy to operate, has low energy consumption, and has readily available raw materials, and is easy to achieve continuous preparation, and has great potential for subsequent control of product morphology. Through this method, the growth of magnesium hydroxide crystals is freed from the limitation of the growth of the electrode film, the reaction zone is expanded, the anisotropy of magnesium hydroxide crystals during the growth process is greatly enhanced, the crystallinity is improved, and the agglomeration of crystal grains is reduced. Compared with the high temperature and high pressure conditions of the hydrothermal method, this method has lower equipment requirements and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 A schematic diagram of the structure of a device for preparing hexagonal flake magnesium hydroxide by continuous electrodeposition;
[0043] In the above figure, 1-electrolytic cell body; 2-salt solution deposition layer; 3-product deposition layer; 4-plate slot; 5-cathode plate; 6-water outlet; 7-pH probe; 8-polytetrafluoroethylene diaphragm; 9-anode plate; 10-temperature control device; 11-filter tank; 12-U-shaped heating rod; 13-conductivity probe; 14-electromagnetic stirrer rotor.
[0044] Figure 2 Schematic diagram of the structure of a conventional electrodeposition device.
[0045] In the above figure, 101 is the electrolytic cell body; 102 is the electrolyte; 103 is the cathode plate; 104 is the diaphragm; 105 is the anode plate;
[0046] Figure 3 This is a SEM image of the final product of hexagonal flaky magnesium hydroxide in Example 1 of the present invention.
[0047] Figure 4 This is a particle size analysis diagram of the final product hexagonal flaky magnesium hydroxide of Example 1 of the present invention.
[0048] Figure 5 This is a SEM image of the final product of Example 2 of the present invention, hexagonal flaky magnesium hydroxide.
[0049] Figure 6 This is a particle size analysis diagram of the final product hexagonal flaky magnesium hydroxide of Example 2 of the present invention.
[0050] Figure 7 This is the SEM image of the final product magnesium hydroxide of Comparative Example 1.
[0051] Figure 8 This is a particle size analysis diagram of the final product magnesium hydroxide of Comparative Example 1.
[0052] Fig. 9 This is the SEM image of the final product magnesium hydroxide of Comparative Example 2.
[0053] Fig.10 This is a particle size analysis diagram of the final product magnesium hydroxide of Comparative Example 2. DETAILED DESCRIPTION
[0054] The present invention is further described below with reference to specific examples, wherein the comparative example is a method for preparing magnesium hydroxide by conventional electrodeposition.
[0055] Example 1
[0056] The device used in this embodiment for preparing hexagonal magnesium hydroxide by continuous electrodeposition is shown in the schematic diagram of the structure. Figure 1, including an electrolytic cell body 1, a polytetrafluoroethylene diaphragm 8 is arranged in the electrolytic cell body 1 to divide the electrolytic cell body 1 into a cathode area and an anode area, and the anode area and the cathode area are only connected through the polytetrafluoroethylene diaphragm 8, a plate slot 4 is arranged in the cathode area for placing a cathode plate 5, and a plate slot 4 is arranged in the anode area for placing an anode plate 9, wherein the cathode plate 5 and the anode plate 9 are both titanium plates coated with titanium dioxide, and the cathode plate 5 and the anode plate 9 are asymmetrically arranged on both sides of the polytetrafluoroethylene diaphragm 8. The cathode plate 5 and the anode plate 9 are both inserted into the electrolyte in the corresponding area, and the distance from the cathode plate of the electrolytic cell to the polytetrafluoroethylene diaphragm is 6 cm.
[0057] A water outlet 6 is provided at the upper part of the side wall of the electrolytic cell in the cathode region; a pH probe 7 is provided in the cathode region, and a heating device is provided in the anode region. The heating device of this embodiment adopts a U-shaped heating rod 12, which is connected to a temperature control device 10. The temperature control device 10 is used to control the heating of the heating rod, thereby controlling the temperature during the electrodeposition process; a stirring device is also provided in the anode region, which is an electromagnetic stirrer rotor 14 provided at the lower part of the anode region in this embodiment; a filter tank 11 is also provided in the anode region for adding bischofite and filtering out impurities. The filter tank 11 is coated with a layer of acid-resistant filter cloth and is placed in the anode region. The raw material is dissolved in the filter tank and diffused into the electrolytic cell under the stirring action of the stirring device, and the filter tank is a detachable structure, which is convenient for feeding, filtering and cleaning of the filter cloth; a conductivity probe 13 is also provided in the electrolyte in the anode region for monitoring the conductivity of the electrolyte.
[0058] Using the above device, the method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition in this embodiment comprises the following steps:
[0059] (1) Sodium chloride was prepared into a solution with a concentration of 0.1 mol / L. The prepared solution was dispersed by ultrasonic and stirred for 0.1 h to make the solution uniformly mixed.
[0060] (2) The solution obtained in step (1) is transferred into the installed reaction electrolytic cell, the temperature control device 10 of the electrolytic cell is turned on, the temperature is set to 30° C., the temperature is raised to the set temperature and the temperature is waited for stabilization.
[0061] (3) When the temperature is stable, add a certain amount of bischofite into the filter tank, turn on the magnetic stirrer and set the speed to 600 r / min, and stir for 30 seconds to make the magnesium ions in the anode area evenly mixed and the concentration is 0.2 mol / L.
[0062] (4) Turn on the power and set the current density to 0.01A / cm 2 , the distance between the plates is 10 cm, the electrodeposition reaction begins, and after a period of time, the product begins to deposit at the bottom of the cathode area.
[0063] (5) During the electrodeposition process, the conductivity of the raw material area is monitored by a conductivity meter, and the pH value of the reaction area is tested every 10 minutes. When the pH value begins to rise after being stable for a period of time and the increase is 1, the feed is circulated and the feed amount is the amount of bischofite required to restore the conductivity of the anode area to its initial value.
[0064] (6) After electrodeposition continued for 4 h, the white precipitate obtained at the bottom of the cathode region was taken out and filtered using a vacuum filter for 10 min. The precipitate was washed twice with deionized water and once with anhydrous ethanol to obtain 3.2 g of the product.
[0065] (7) drying the washed product in step (6) at 100° C. for 10 h to obtain a hexagonal flaky magnesium hydroxide product.
[0066] The obtained product was tested and its SEM image is shown in Figure 3 ,pass Figure 3 It can be seen that the magnesium hydroxide presents a hexagonal flake structure with clear edges, and the grain size is about 100 nanometers and is evenly distributed. The particle size analysis diagram of the obtained hexagonal flake magnesium hydroxide is shown in Figure 4 ,pass Figure 4 It can be seen that the laser particle size of the product is small, the median particle size is 12.4μm, and the degree of agglomeration is low.
[0067] Example 2
[0068] The apparatus for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition in this embodiment is the same as that in Example 1.
[0069] The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition of this embodiment comprises the following steps:
[0070] (1) Sodium chloride was prepared into a solution with a concentration of 0.15 mol / L. The prepared solution was dispersed by ultrasonic and stirred for 0.1 h to make the solution uniformly mixed.
[0071] (2) The solution obtained in step (1) was transferred into the installed reaction electrolytic cell, the temperature control device of the electrolytic cell was turned on, the temperature was set to 35° C., the temperature was raised to the set temperature and the temperature was waited for stabilization.
[0072] (3) When the temperature is stable, add a certain amount of bischofite into the filter tank, turn on the magnetic stirrer and set the speed to 600 r / min, and stir for 30 seconds to make the magnesium ions in the anode area evenly mixed and the concentration is 0.2 mol / L.
[0073] (4) Turn on the power and set the current density to 0.008A / cm 2 , the distance between the plates is 10 cm, the electrodeposition reaction begins, and after a period of time, the product begins to deposit at the bottom of the cathode area.
[0074] (5) During the electrodeposition process, the conductivity of the raw material area is monitored by a conductivity meter, and the pH value of the reaction area is tested every 10 minutes. When the pH value begins to rise after being stable for a period of time and the increase is 1, the feed is circulated and the feed amount is the amount of bischofite required to restore the conductivity of the anode area to its initial value.
[0075] (6) After the electrodeposition lasted for 5 h, the white precipitate obtained at the bottom of the cathode region was taken out, filtered, and washed twice with deionized water and once with anhydrous ethanol to obtain 3.6 g of the product.
[0076] (7) drying the washed product in step (6) at 100° C. for 10 h to obtain a hexagonal flaky magnesium hydroxide product.
[0077] The obtained product was tested and its SEM image is shown in Figure 5 ,pass Figure 5 It can be seen that the magnesium hydroxide presents a hexagonal flaky structure with clear edges. Compared with Example 1, the crystal grains are increased to about 200 nanometers and are evenly distributed. The particle size analysis diagram of the obtained hexagonal flaky magnesium hydroxide is shown in FIG. Figure 6 ,pass Figure 6 It can be seen that the laser particle size of the product is small, the median particle size is 7.8μm, and the degree of agglomeration is low.
[0078] Example 3
[0079] The same as Example 1, except that in step (2), the temperature of the electrodeposition process is set to 45°C, the product grain size is enlarged, the hexagonal lamellar structure is more standard, the thickness is increased, the dispersion is good, and the laser particle size is small and the agglomeration is further weakened.
[0080] Example 4
[0081] Same as Example 2, except that (1) the molar concentration of the sodium chloride aqueous solution is 0.05 mol / L; (2) in step (3), the magnetic stirrer is set to a speed of 1000 r / min and stirred for 60 s to uniformly mix the magnesium ions in the anode region; (3) the current density is 0.006 A / cm 2 , the experimental phenomena and results are the same as those in Example 2, with no significant changes.
[0082] Example 5
[0083] Same as Example 2, except that: (1) in step (3), a certain amount of bischofite was added to the filter tank, the magnetic stirrer was turned on and the speed was set to 600 r / min, and the stirring was performed for 30 s to make the magnesium ions in the anode region uniformly mixed and the concentration was 0.3 mol / L; (2) the current density was set to 0.015 A / cm 2 . Then 4.0g of product is obtained, and the yield is increased.
[0084] Example 6
[0085] Same as Example 2, except that (1) the molar concentration of the sodium chloride aqueous solution is 0.2 mol / L; (2) the current density is 0.01 A / cm 2 , the plate spacing is set to 12 cm, then the experimental phenomena and results are the same as those in Example 2, with no significant changes.
[0086] Example 7
[0087] Same as Example 2, except that: (1) in step (3), the magnesium ions in the anode region are uniformly mixed and have a concentration of 0.1 mol / L; (2) the current density is 0.02 A / cm 2 , the electrodeposition lasted for 10 hours. Then 6.8 g of product was obtained, the yield increased, and there was no significant change in other aspects.
[0088] Example 8
[0089] The same as Example 2, except that: (1) in step (3), the magnesium ions in the anode region are uniformly mixed and have a concentration of 0.5 mol / L; (2) the product after washing in step (6) is dried at a temperature of 120° C. for 12 h. The experimental phenomena and results are the same as those in Example 2, with no significant changes.
[0090] Example 9
[0091] The same as Example 1, except that in step (2), the temperature of the electrodeposition process is set to 60°C, the cell voltage is reduced, the reaction rate is accelerated, the grains are larger and the crystallinity is higher, the particle size distribution is more concentrated, and the size is uniform.
[0092] Comparative Example 1
[0093] The schematic diagram of the device structure used in this comparative example is shown in Figure 2 , comprising an electrolytic cell body 101, a diaphragm 104 is arranged in the electrolytic cell body 101 to divide the electrolytic cell body into a cathode area and an anode area, a cathode plate 103 is arranged in the cathode area, an anode plate 105 is arranged in the anode area, and an electrolyte 102 is added in the electrolytic cell body;
[0094] (1) Only magnesium chloride solution is used as the electrolyte. Bischofite (MgCl2·6H2O) is prepared into a magnesium chloride solution with a concentration of 0.4 mol / L. The prepared magnesium chloride solution is ultrasonically dispersed and stirred for 0.1 h to make the solution uniformly mixed.
[0095] Add the prepared magnesium chloride solution into the electrolytic cell body and evenly distribute it in the cathode area and the anode area;
[0096] (2) Turn on the power and set the current density to 0.04A / cm2 , the distance between the plates is 4 cm, and the electrodeposition reaction begins. After a period of time, the product begins to deposit on the plates first, and then falls off and sinks to the bottom of the cathode area when it reaches a certain thickness.
[0097] (3) After the electrodeposition lasted for 4 h, the white precipitate at the bottom of the cathode in the cathode region was removed, filtered, and washed twice with deionized water and once with anhydrous ethanol.
[0098] (4) drying the washed product in step (3) at 100° C. for 10 h to obtain a magnesium hydroxide product.
[0099] The obtained product was tested and its SEM image is shown in Figure 7 ,pass Figure 7 It can be seen that magnesium hydroxide presents a large flake structure with unclear edges and severe adhesion between grains. The diameter-to-thickness ratio is very high, with a diameter of up to 600nm and a thickness of only 30nm. The morphology and particle size are uneven. The particle size analysis diagram of the obtained magnesium hydroxide is shown in Figure 8 ,pass Figure 8 It can be seen that the laser particle size of the product is very large, the median particle size is as high as 97μm, and the agglomeration is very serious.
[0100] Comparative Example 2
[0101] (1) Only magnesium chloride solution is used as the electrolyte. Bischofite (MgCl2·6H2O) is prepared into a magnesium chloride solution with a concentration of 0.3 mol / L. The prepared magnesium chloride solution is ultrasonically dispersed and stirred for 0.1 h to make the solution uniformly mixed.
[0102] Add the prepared magnesium chloride solution into the electrolytic cell body and evenly distribute it in the cathode area and the anode area;
[0103] (2) Turn on the power and set the current density to 0.02A / cm 2 , the distance between the plates is 4 cm, and the electrodeposition reaction begins. After a period of time, the product begins to deposit on the plates, and when it reaches a certain thickness, it falls off and sinks to the bottom of the cathode area.
[0104] (3) After electrodeposition continued for 5 h, the white precipitate obtained at the bottom of the cathode region was removed, filtered, and washed twice with deionized water and once with anhydrous ethanol.
[0105] (4) drying the washed product in step (3) at 100° C. for 10 h to obtain a magnesium hydroxide product.
[0106] The obtained product was tested and its SEM image is shown in Fig. 9 ,pass Fig. 9It can be seen that magnesium hydroxide is in the form of thin flakes with unclear edges and severe adhesion between grains, and is connected in a network structure. The dispersion is very poor, and the morphology and particle size are uneven. The particle size analysis diagram of the obtained magnesium hydroxide is shown in Fig.10 ,pass Fig.10 It can be seen that the laser particle size of the product is very large, with a median particle size of up to 109μm, and agglomeration is very serious.
[0107] In the scanning electron microscope image, it can be seen that the comparative example 1 ( Figure 7 ), Comparative Example 2 ( Fig. 9 ) The morphology of magnesium hydroxide is a continuous network structure, or a thin sheet with irregular edges, and the grains are severely adhered to each other, while Example 1 of the present invention ( Figure 3 )、Example 2( Figure 5 The morphology of magnesium hydroxide of ) is a hexagonal sheet structure with good grain dispersion and regular edges. It can be seen from the particle size distribution diagram that the comparative example 1 ( Figure 8 ), Comparative Example 2 ( Fig.10 ) The secondary particle size of magnesium hydroxide is very large, with a median particle size of about 100 μm, severe agglomeration, and poor dispersibility, while Example 1 ( Figure 4 )、Example 2( Figure 6 ) The median particle size of magnesium hydroxide is about 10 μm, which is nearly 10 times lower than that of the comparative example, and has good dispersibility.
[0108] Comparative Example 3
[0109] The filtration performance of the magnesium hydroxide prepared by the sodium hydroxide precipitation method is that the filtration time for 3.2g of the product is 1 hour. The filtration rate of Example 1 is 6 times faster than that of the sodium hydroxide precipitation method.
[0110] Comparative Example 4
[0111] The same as Example 1, except that the electrodeposition process is carried out at room temperature, the product grains are smaller, the morphology is uneven, and they are easily agglomerated, resulting in poor dispersibility and increased laser particle size.
[0112] Comparative Example 5
[0113] Same as Example 1, except that bischofite and sodium chloride are directly mixed, water is added to prepare a mixed solution with a concentration of 0.1 mol / L sodium chloride and 0.3 mol / L magnesium chloride, and Figure 2 The electrodeposition was carried out in a conventional electrolytic cell. The experiment was similar to that in comparative example 2. The product grew on the electrode plate, fell off after a period of time and settled to the bottom. However, the particle size of the magnesium hydroxide laser was reduced to 38 μm, but it was still relatively large.
[0114] Comparative Example 6
[0115] The molar concentration of the prepared sodium chloride aqueous solution is 0.3 mol / L, and the other conditions are the same as in Example 1. The proportion of magnesium ions migrating to the cathode plate is reduced, resulting in an increase in the migration of hydroxide ions to the diaphragm. The reaction mainly occurs near the diaphragm, the product blocks the diaphragm, and the electrodeposition process cannot proceed normally.
[0116] Comparative Example 7
[0117] The molar concentration of the prepared sodium chloride aqueous solution is 0.01 mol / L, and the other conditions are the same as in Example 1. However, too many magnesium ions migrate to the cathode plate, so that the reaction mainly occurs near the plate, the product adheres to the plate, the product is severely agglomerated, and the electrodeposition process cannot proceed normally.
[0118] Comparative Example 8
[0119] No stirring is provided in the anode region, and other conditions are the same as those in Example 1. However, due to the slow dissolution rate of bischofite in static state and the gravity sedimentation of the salt solution, the anode region solution is uneven, the mass transfer efficiency is low, and the electrodeposition process cannot proceed normally.
[0120] Comparative Example 9
[0121] After stirring in the anode region, the magnesium ions are evenly distributed in the anode region and the molar concentration is 0.05 mol / L. The other conditions are the same as in Example 1. However, since the magnesium ion concentration is too low, the electromigration mass transfer is mainly based on sodium ions, resulting in the migration of hydroxide to the anode and being consumed at the anode. The reaction efficiency is extremely low and the electrodeposition process cannot proceed normally.
[0122] The above embodiments are only used to illustrate the technology provided by the present invention, so that relevant persons familiar with such technology can understand and apply the content of the present invention, and are not intended to limit the technical solution. Any modification or equivalent replacement of the technical solution of the present invention, which does not deviate from the scope and purpose of the solution of the present invention, should be included in the scope of the rights required by the present invention.
Claims
1. A method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition, using a device for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition, the device comprising an electrolytic cell, a polytetrafluoroethylene diaphragm is arranged in the electrolytic cell body to divide the electrolytic cell body into a cathode area and an anode area, and the anode area and the cathode area are connected only through the diaphragm, a cathode plate is arranged in the cathode area, an anode plate is arranged in the anode area, and a water outlet is arranged on the upper part of the side wall of the electrolytic cell body in the cathode area; the electrolytic cell is also provided with a heating device for controlling the temperature during the electrodeposition process; a stirring device is also arranged in the anode area, and a filter tank is also arranged in the anode area for adding bischofite and filtering out impurities; the cathode plate and the anode plate are distributed and designed to be an asymmetric structure; It is characterized in that The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition comprises the following steps: S1: prepare a sodium chloride aqueous solution with a molar concentration of 0.05-0.2 mol / L; S2: adding sodium chloride aqueous solution into the electrolytic cell, heating it to 30-60°C, adding bischofite into the anode region after the temperature stabilizes, and stirring, so that the magnesium ions in the anode region are evenly distributed and the molar concentration is 0.1-0.5 mol / L; wherein a diaphragm is provided in the electrolytic cell, dividing the electrolytic cell into an anode region and a cathode region connected only by the diaphragm; the anode plate is provided in the anode region, and the cathode plate is provided in the cathode region; S3: Connect the anode plate and cathode plate to the power supply and set the current density to 0.006~0.02A / cm 2 The distance between the cathode plate and the anode plate is 6 to 12 cm. The electrodeposition is carried out for 4 to 12 hours. A white precipitate is obtained in the cathode area. The precipitate is filtered, washed and dried to obtain hexagonal flaky magnesium hydroxide.
2. The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition according to claim 1, characterized in that: In the S2, the stirring has a stirring rate of 200 to 1000 r / min and a stirring time of 30 to 60 s.
3. The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition according to claim 1, characterized in that: In the S3, the drying temperature is 60-120° C., and the drying time is 6-12 hours.
4. The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition according to claim 1, characterized in that: During the electrodeposition process, the feeding time of bischofite circulation is determined according to the change of pH value in the cathode area. The specific determination method is: when the pH value starts to increase after being stable and the increase is 1, the feeding is carried out.
5. The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition according to claim 1, characterized in that: During the electrodeposition process, the conductivity of the electrolyte in the anode region is monitored according to the conductivity to determine the feeding amount of bischofite for circulation, and the feeding amount is the mass of bischofite that makes the molar concentration of magnesium ions in the anode region account for 0.1 to 0.5 mol / L.
6. The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition according to claim 1, characterized in that: A pH probe is arranged in the cathode region; a conductivity probe is arranged in the anode region for monitoring the conductivity of the electrolyte.
7. The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition according to claim 1, characterized in that: The polytetrafluoroethylene diaphragm is a polytetrafluoroethylene film with a pore size of 0.5 to 10 μm.
8. The method for preparing hexagonal flaky magnesium hydroxide by continuous electrodeposition according to claim 1, characterized in that: The distance between the cathode plate and the polytetrafluoroethylene diaphragm is 55% to 70% of the distance between the plates.
Citation Information
Patent Citations
Method for preparing magnesium hydroxide hexagonal nanosheets
CN103803601A
A method for preparing uniform hexagonal sheet-like nano-magnesium hydroxide by hydration
CN107804863B
Method for preparing hexagonal flaky flame-retardant magnesium hydroxide from natural hydromagnesite
CN113548682A